PENGARUH MODEL PEMBELAJARAN CONCEPT ATTAINMENT TERHADAP KEMAMPUAN KOMUNIKASI DAN PEMAHAMAN KONSEP SISWA PADA MATERI SISTEM REPRODUKSI - Retno, Yulilina; Rusdi, R; Amalia, A (Universitas Negeri Jakarta, 2016)
Students need to have one of the science process skills in learning which is communication skill. Based on observation it was known that not every student had the same communication capabilities, both in oral and written. This is due to lack of student’s understanding about the concept of the material which being studied. Application of Concept Attainment learning model was expected to train students how to construct concepts on their own and be able to express it verbally. This study was aimed to determine the influence of the Concept Attainment learning model to communication skills and student’s understanding of Reproductive System material concept. This research was conducted in SMA Negeri 16 Jakarta on May 2015. This research used quasi-experimental method. The sample were 30 students each in the experimental class and control class by using simple random sampling. The instrument for this research was a written communication skills post test, understanding of concepts post test, and the observation of verbal ability. The analysis prerequisite test was the test of normality with the Kolmogorov-Smirnov and homogeneity test with F test. Based on the calculations, the data were normally distributed and homogeneous. Hypothesis test using the test results showed that Ho was rejected at α 0.05. It means that there was an influence of Concept Attainment learning model of the communication skills and student’s understanding concept on Reproductive System.